DISTRIBUTION OF LIPID PROFILE VALUES IN ECONOMICALLY ACTIVE MEN AND WOMEN IN RUSSIAN FEDERATION: RESULTS OF THE ESSE-RF STUDY FOR THE YEARS 2012-2014 - A. N. Meshkov; A. I. Ershova; A. D. Deev; V. A. Metelskaya; Yu. V. Zhernakova; O. P. Rotar; S. A. Shalnova; S. A. Boytsov (Кардиоваскулярная терапия и профилактика, 2017)
Elevated level of plasma cholesterol, together with arterial hypertension, is the main modifiable factor of cardiovascular diseases (CVD) development. Monitoring of lipid levels at populational level is an important instrument of the prevention medicine, applied for CVD populational risk assessment.Aim. Blood lipid levels assessment, with the data obatined during epidemiological study “ESSE-RF” (Epidemiology of cardiovascular diseases in various regions of Russian Federation) in 13 regions of Russia.Material and methods. In the study, the patients were included, of 25-64 y.o. All participants underwent specimens collection for total cholesterol (TC), triglycerides (TG), high density lipoproteides cholesterol (HDL-C) and low density lipoproteides cholesterol (LDL-C) by enzymatic methods on automatic analyzer Abbott Architect 8000. Also, in all the participants, hypolipidemic therapy was evaluated.Results. Totally, 21167 persons included into analysis, 7937 males and 13230 females. 807 (3,81%) had been taking hypolipidemic therapy and were ruled out from further analysis. Mean age 44±12 and 47±11 y.o., respectively. Mean values for men were TC 5,31±1,15 mM/L, TG 1,58±1,24 mM/L, HDL-C 1,30±0,33 mM/L and LDL-C 3,38±0,99 mM/L (7643 persons), for women — 5,48±1,18 mM/L, 1,36±0,85 mM/L, 1,47±0,35 mM/L and 3,42±1,04 mM/L, respectively (12717 persons). In the study we present percentile variations of the studied groups by the measured levels of TC, TG, HDL-C, LDL-C according to the age and sex. There were moderate correlations found of HDL-C with age and sex (r=0,34, p=0,000) and LDL-C (r=0,33, p=0,000). Correlation of TG with age and sex was low, but significant (r=0,18, p=0,000). There was no correlation of HDL-C with age and sex (r=-0,002, p=0,740). Also, a high prevalence is shown for severe lipid disorders. 23% of the participants had severely increased TC level (>6,2 mM/L), and 20,6% — of LDL-C (>4,2 mM/L). Severe increase of TG (>5,0 mM/L) was found much more rarely (1,1%).Conclusion. In the ESSE-RF study the prevalence of significant lipid disorders was shown as high, that demands respective prevention and management. This study might be a starting point for lipids populational dynamics analysis in Russia.